Emissions taxes and abatement regulation under uncertainty - Vidar Christiansen; Stephen Smith (Center for Economic Studies and ifo Institute (CESifo), 2013)
We consider environmental regulation in a context where firms invest in abatement technology under conditions of uncertainty about subsequent abatement cost, but can subsequently adjust output in the light of true marginal abatement cost. Where an emission tax is the only available instrument, policy faces a trade-off between the incentive to invest in abatement technology and efficiency in subsequent output decisions. More efficient outcomes can be achieved through combined use of tax and mandated use of a given abatement technology or through combining the tax with an abatement technology investment subsidy. We compare the properties of the two potential supplements to the emissions tax.
Keywords: H23; 330; externalities; Pigouvian taxes; subsidies; regulation